Messenger from Mystery : A Novel - Trakas, Deno (Story river books., 2017)
Deno Trakas's novel Messenger from Mystery features English graduate student Jason "Jay" Nichols, a third-generation Greek American who claims to be named after the heroic Argonaut leader despite an introspective and self-absorbed nature. On the cusp of his transition into adulthood and from student to teacher, Jay still lives primarily in his own thoughts and studies. Having been an activist in college, he considers himself knowledgeable about local and global politics, but when the Iranian hostage crisis begins while he is teaching students from Iran, he realizes that his understanding of geopolitical conflict is naive and superficial. Jay becomes infatuated with one of his students, Azadeh "Azi" Ghotbzadeh, whose cousin is the foreign minister of Iran and wants to work with the United States to resolve the crisis, which makes Azi vulnerable to manipulation and other threats. Her family insists that she return to Iran at the end of the semester, but before she goes, she spends a week with Jay, and they fall in love. When Azi leaves, Jay is crushed. When Hamilton Jordan, one of President Jimmy Carter's closest aides, learns that his college friend Jay has a close relationship with a woman with access to the inner circles of the Ayatollah, Jordan enlists Jay's help. At first Jay is a simple intermediary, but when his mission goes terribly wrong and Azi is put in mortal peril, Jay finds himself in the unlikely and uncomfortable role of rescuer. Aided by a CIA operative and Jay's literary hero, he travels to Iran to free Azi from her captors. Like the award-winning film Argo, Messenger from Mystery harks back to the difficult final years of the Carter administration and looks closely at the hostage crisis, which captured the attention of the world for 444 days, garnered its own news show, ensured the defeat of Carter and the victory of Reagan, and frayed any American confidence regained after Vietnam and Watergate. A story of love, politics, terrorism, and heroism, Messenger from Mystery mixes accurate, fascinating history with convincing, engaging imagination. Trakas's novel depicts the human heart in conflict with itself as well as a subtle, thoughtfully rendered critique of U.S.-Middle East relations of the era, still relevant today.